2008
DOI: 10.2202/1553-3840.1152
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Antioxidant Activity and Lipid Peroxidation of the Leaves of Vernonia amygdalina

Abstract: This study evaluated the in vitro antioxidant activity of water (VAWE) and ethanol (VAEE) extracts of the leaf of Vernonia amygdalina. The antioxidant activity of each extract was evaluated using various radicals or oxidation systems. The total phenolic or flavonoid contents and their correlation with total antioxidant activity were also evaluated. VAEE exhibited antioxidant scavenging potential comparable to butylated hydroxyanisole (BHA), but higher than butylated hydroxytoluene (BHT) or VAWE. The total anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 0 publications
2
19
0
1
Order By: Relevance
“…[10,11,12] It has been reported that the beneficial effect of V. amygdalina may be attributed at least in part to its antioxidant action. [13] …”
Section: Introductionmentioning
confidence: 99%
“…[10,11,12] It has been reported that the beneficial effect of V. amygdalina may be attributed at least in part to its antioxidant action. [13] …”
Section: Introductionmentioning
confidence: 99%
“…Also the aqueous and ethanolic extract of VA has further been shown to have potent antioxidant properties as they were able to inhibit bleaching of Bcarotene, oxidation of linoleic acid and lipid peroxidation induced by Fe 2+/ ascorbate in a rat liver microsomal preparation. This study showed that the antioxidant activity of the ethanolic extracts was higher than that of the aqueous extracts, and compared favourably with synthetic antioxidant BHT and BHA [29]. However another study reported that methanol extract displayed highest antioxidant activity followed by acetone and water extract [30].…”
Section: Vernonia Amygdalina (Va)mentioning
confidence: 64%
“…The study demonstrated that the antioxidant activity of the ethanolic extract was higher than that of aqueous extracts but compared favourably with synthetic antioxidants like butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) (Owolabi et al, .2008). …”
Section: Antioxidant Activitymentioning
confidence: 99%